Pengaruh Promosi, Aksesibilitas Dan Fasilitas Wisata Terhadap Minat Kunjungan Wisata Di Pantai Sedahan Kabupaten Gunungkidul - Ati Maflakha (Universitas Mercu Buana, 2022)
The development of tourism in Indonesia is currently being pushed to become a sector that contributes greatly to economic development and improving people's welfare. One of the tourism places that experiences fluctuations in the number of visitors so that it affects economic development is Sedahan Beach, Gunungkidul Regency. This study aims to examine and analyze the effect of promotion on interest in tourist visits, the effect of accessibility on interest in tourist visits, and the influence of tourist facilities on interest in tourist visits. Design This study uses a causal research design with a quantitative research approach. The population in this study were domestic/domestic tourists who had visited Sedahan Beach, Gunungkidul Regency. The sampling technique was purposive sampling, the number of samples was 384 people. Data collection techniques using a questionnaire. Data analysis in this study used multiple linear regression. The results showed that there was a positive and significant effect of promotion on interest in visiting, there was a significant positive effect of the accessibility variable on interest in visiting, there was a significant positive effect of facilities on interest in visiting.